Prevalence and predictive determinants of adherence to vaccination against COVID-19 among mothers who gave birth in the last two years in Morocco - Fatima Zohra Benayad; Rachid Razine; Abbas Ermilo Haroun; Ahmed Oubaasri; Elmostafa El Fahim; Redouane Abouqal; Majdouline Obtel (Elsevier, 2023)
Background and aim: Vaccination against COVID-19 was one of the most important resolute to stop the spread of the pandemic; however, its acceptance was controversial especially by pregnant and lactating women. This study aims to assess the prevalence of vaccination among participants as well as to explore the determinants of reluctance or adherence to vaccination among this population, and to investigate the intention towards vaccination among the unvaccinated. Method: This is a cross-sectional study conducted among mothers (n = 458) residing in the prefecture of Skhirat-Temara in Morocco, and who have children aged between one month to 2 years, the survey was conducted on the basis of a semi-structured questionnaire. Result: The prevalence of vaccination among the participants was 61.8%, although they were all vaccinated after their delivery. Among the unvaccinated, 64% wanted to be vaccinated either because they believed the vaccines were useful or because they wanted to get the vaccine pass, while 36% absolutely refused to be vaccinated due to lack of sufficient information on the efficacy and safety of new vaccines against COVID-19. The age of the last child (p < 0.001) and no gestational diabetes during pregnancy (p = 0.016) were found to be positive predictors of vaccination adherence; however, the average or the high monthly income (p = 0.003) and the lack of medical coverage (p = 0.046) were predictive factors limiting adherence to vaccination. Conclusion: The results of this study suggest that public health decision-makers need to increase awareness of the benefits of vaccination and to address the economic and social factors limiting access to COVID-19 vaccination.